2019
DOI: 10.1111/dom.13826
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term efficacy and safety of combined insulin and glucagon‐like peptide‐1 therapy: Evidence from the LEADER trial

Abstract: Aim Glucagon‐like peptide‐1 receptor agonist (GLP‐1RA) and insulin combination therapy is an effective treatment option for type 2 diabetes, but long‐term data are lacking. The aim was to assess the long‐term efficacy of the GLP‐1RA liraglutide in subgroups by insulin use in the LEADER trial. Materials and Methods LEADER assessed cardiovascular (CV) safety and efficacy of liraglutide (1.8 mg) versus placebo (plus standard of care therapy) in 9340 patients with type 2 diabetes and high risk of CV disease, for u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…SU utilization has declined owing to the introduction of Glp1 agonists and DPP4 inhibitors in the diabetes pharmacopeia. However, the latter drugs are not immune to secondary failures either (28)(29)(30)(31)(32) and suffer from poor patient adherence (33)(34)(35). In addition, as top-line findings from the comparative effectiveness glycemia reduction approaches in type 2 diabetes study (GRADE) study demonstrate, the 5-year therapeutic failure rates of SU (72%) are comparable to those of other secretagogues or insulin (67 to 77%).…”
Section: Discussionmentioning
confidence: 99%
“…SU utilization has declined owing to the introduction of Glp1 agonists and DPP4 inhibitors in the diabetes pharmacopeia. However, the latter drugs are not immune to secondary failures either (28)(29)(30)(31)(32) and suffer from poor patient adherence (33)(34)(35). In addition, as top-line findings from the comparative effectiveness glycemia reduction approaches in type 2 diabetes study (GRADE) study demonstrate, the 5-year therapeutic failure rates of SU (72%) are comparable to those of other secretagogues or insulin (67 to 77%).…”
Section: Discussionmentioning
confidence: 99%
“…Why should we then care whether we can revamp it? For three main reasons: first, with time it has become apparent that Glp1 agonists and DPP4 inhibitors are not immune to secondary failures [29][30][31][32][33] , and the former suffer from poor patient adherence [34][35][36] . Second, as topline findings from the comparative effectiveness GRADE study demonstrate, the five-year therapeutic failure rates of SU (72%) are comparable with those of other secretagogues or insulin (67 to 77%).…”
Section: Cyb5r3 Activator Thii Rescues Secondary Failure To Glbmentioning
confidence: 99%
“…Clinical trials have shown that this strategy, compared to basal-bolus regimens, allows equal or better glycaemic control with lower risk of hypoglycaemia, has a beneficial effect on body weight and results in a reduction in total daily insulin dose [9][10][11][12][13]. Furthermore, in this population of patients, GLP-1RA can reduce the risk of adverse cardiovascular outcomes [14].…”
Section: Introductionmentioning
confidence: 99%